The experience of person with chronic renal disease in hemodialysis: meanings attributed for the patients - Claudinei José CJGC Gomes Campos; Egberto Ribeiro Turato (Online Brazilian Journal of Nursing, 2007)
Hemodialysis treatment received by chronic renal patients is known to be distressing and to impose a set of biological, psychological and social limitations(1). This work aimed to study how renal patients experience disease and hemodialysis treatment in a specialized service of a State University Hospital. As specific aims they were to analyze and understand the meanings the patient attributes to disease and treatment; to know the bio-psychosocial limitations experienced by the renal patient undergoing hemodialysis and to understand how they cope with them besides to analyze under the patient viewpoint how he realizes the treatment received from health professionals and their interpersonal relationships. The method used was clinical qualitative (2), using semi guided interview as instrument of data collection (3). The sample of 7 patients was obtained by intentional sampling and data saturation and the interviews were audio recorded and fully transcripted. The data were analyzed according the thematic content (4). Four categories were obtained: 1 – the experiences and meanings of hemodialysis for the patient, 2- psychological aspects involved, 3- physical and social limitations caused by the disease and treatment and 4 – the relationship with the hemodialysis team. The conclusions were that chronic renal patient attributes diverse meanings to hemodialysis treatment and that survival appeared as the main meaning for such event. The renal disease and hemodialysis treatment cause individual emotional alterations in different degrees that can interfere in the treatment evolution. Patients have difficulties in social and professional life, relations with friends and family members besides somewhat social discrimination. On the interpersonal relation with the health team, patients indicate the need for more attention and willingness to be listened more (5).
Referências Bibliográficas
1 - Matta GC. Hospitais, subjetividade e glomérulos inoperantes: da doença renal ao renal crônico. (Dissertação). Rio de Janeiro (RJ): Instituto de Medicina Social da Universidade do Estado do Rio de Janeiro; 1998.
2 - Turato EG. Introdução à metodologia da pesquisa clínico-qualitativa: definição e principais características. Revista Portuguesa de Psicossomática 2000; 2(1):93-108.
3 - Kvale S. Interviews: an introduction to qualitative research interviewing. Thousand Oaks: SAGE; 1996.
4 - Downe-Wamboldt B. Content analysis: method, applications, and issues. Health Care Women Int, 1992; 13(3):313-21.
5 - Perestrello D. A Medicina da pessoa. 4a ed., São Paulo (SP): Atheneu; 1996.